ANALISIS KEMAMPUAN REPRESENTASI MATEMATIS SISWA SMK 3 AL-WASHLIYAH MEDAN PADA MATERI STATISTIKA - Aurelya Nasution, Chintya Dea; Puspita Sari, Della; Aisyah, Siti; ., Ramadhani (JURNAL MathEdu (Mathematic Education Journal), 2023)
The research aims to determine the level of mathematical representation ability of SMK students in statistics material. Through this research will be analyzed the level of students' mathematical representation abilities which are grouped into high, medium and low, as well as students' mistakes in solving problems on statistics material which focuses on the mean, median and mode. The research subjects were 3 class XII students, all of whom consisted of female students. Research includes qualitative research. Data collection techniques using tests and interviews. The results showed that the representational abilities of SMK students were moderate at 62%. Student errors included (1) students were not careful in completing calculations properly (2) students chose sentences in solving illogical questions and preferred to use equations. (3) Student answers written by students are not clearly visible..